2019
DOI: 10.1002/jcla.22963
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis and clinical characterization of Iranian patients with mucopolysaccharidosis type I

Abstract: BackgroundMucopolysaccharidosis type I (MPSI) is a rare autosomal recessive disorder caused by a deficiency of α‐l‐iduronidase (IDUA) encoded by the IDUA gene. We examined the mutation spectrum of the IDUA gene to explain the clinical, biochemical, and molecular features in 21 Iranian patients with MPSI.MethodsSanger sequencing was used to measure the IDUA gene sequence in the coding region and exon‐intron boundaries. We recorded the clinical findings of studied patients at the first diagnosis of disease and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Biochemical assays already described for these variants showed essentially no activity in homozygotes (13), concord-ant with Hurler phenotype, in our patients being observed a very low activity for the enzyme, the clinical phenotype being also Hurler syndrome. The incidence of p.Q70* (c.208C>T) mutation, 3/8 alleles of pathological variants of IDUA gene alleles identified in our group is according to results reported by other studies (5,(14)(15)(16)(17)(18)(19). In F4, compound heterozygous p.Q70*(c.208C>T), the second variant is a deletion located on exon 1 (p.S16_A19del, 46_57delTCGCTCCTGGCC), described by Bunge in 1994, as a mutation that induces a severe phenotype (3,20).…”
Section: Discussionsupporting
confidence: 89%
“…Biochemical assays already described for these variants showed essentially no activity in homozygotes (13), concord-ant with Hurler phenotype, in our patients being observed a very low activity for the enzyme, the clinical phenotype being also Hurler syndrome. The incidence of p.Q70* (c.208C>T) mutation, 3/8 alleles of pathological variants of IDUA gene alleles identified in our group is according to results reported by other studies (5,(14)(15)(16)(17)(18)(19). In F4, compound heterozygous p.Q70*(c.208C>T), the second variant is a deletion located on exon 1 (p.S16_A19del, 46_57delTCGCTCCTGGCC), described by Bunge in 1994, as a mutation that induces a severe phenotype (3,20).…”
Section: Discussionsupporting
confidence: 89%
“…There are recently published mutations specific for some nations, including Yemen (c.657delA) [ 69 ], Pakistan (p.L303P and c.1456G > T) [ 54 , 70 ], and Tunisia (c.1650 + 1G > T) [ 71 ]. Additionally, Iran has the novel widespread mutation p.Y109H, which accounts for 15.6% of identified mutations [ 72 ].…”
Section: Mutationsmentioning
confidence: 99%
“…Although there have been a few studies published in recent years that have contributed to our understanding of the molecular causes of MPS in Iran, the patient pool in those studies was considerably smaller than that of ours. Overall, 18 studies have reported molecular characterization of Iranian MPS patients, comprising 46 MPS I patients, 34 MPS VI patients, 19 MPS III patients, 4 MPS II patients, 4 MPS IV patients, and 1 MPS VII patient (Abbasi et al, 2017; Alaei et al, 2020; Aminzadeh et al, 2019; Jafaryazdi et al, 2019; Kamranjam & Alaei, 2019; Khorrami et al, 2019; Malekpour et al, 2018; Mansour et al, 2007; Martins et al, 2019; Mosallanejad et al, 2020; Nouri et al, 2012; Salehi, 2004; Seyedhassani et al, 2015; Shafaat et al, 2020; Taghikhani et al, 2019; Valstar, Bertoli‐Avella, et al, 2010; Yassaee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Variome MPS Database Alaei et al, 2020;Aminzadeh et al, 2019;Jafaryazdi et al, 2019;Kamranjam & Alaei, 2019;Khorrami et al, 2019;Malekpour et al, 2018;Mansour et al, 2007;Martins et al, 2019;Mosallanejad et al, 2020;Nouri et al, 2012;Salehi, 2004;Seyedhassani et al, 2015;Shafaat et al, 2020;Taghikhani et al, 2019;Valstar, Bertoli-Avella, et al, 2010;Yassaee et al, 2017). American Caucasian, Austrian, Macedonian, Turkish, Greek, and Indian population (Bidchol et al, 2014;Morrone et al, 2014).…”
Section: Details Of the Variants Identified In This Study Are Availab...mentioning
confidence: 99%